1961
DOI: 10.1029/jz066i012p04003
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Van Allen radiation regions during August and September 1959

Abstract: This paper shows that any particles affected by the Capetown magnetic anomaly do not have trajectories that would pass through the position of the experimentally observed minimum in the outer belt. Therefore, the minimum cannot be taken as evidence either for the effect of the anomaly on the trapped radiation or for support of the neutron albedo source for the outer zone electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Bifurcation of the outer zone (i.e., two intensity peaks due to energetic electrons) was not observed in the first five months of Explorer 14 data presently under discussion. Bifurcation of the outer zone has been previously observed near the geomagnetic equatorial plane with instruments aboard Explorer 6 [Hoffman, 1961] and on Explorer 12 [Freeman, 1964] Figures 2, 3, and 4). Hence, it appears that such protons are markedly less sensitive to geomagnetic disturbances than are electrons (see Figure 4 in particular).…”
Section: The Above Sequence Of Phenomena Is Consistentmentioning
confidence: 57%
“…Bifurcation of the outer zone (i.e., two intensity peaks due to energetic electrons) was not observed in the first five months of Explorer 14 data presently under discussion. Bifurcation of the outer zone has been previously observed near the geomagnetic equatorial plane with instruments aboard Explorer 6 [Hoffman, 1961] and on Explorer 12 [Freeman, 1964] Figures 2, 3, and 4). Hence, it appears that such protons are markedly less sensitive to geomagnetic disturbances than are electrons (see Figure 4 in particular).…”
Section: The Above Sequence Of Phenomena Is Consistentmentioning
confidence: 57%
“…On the recovery phase the intensity and average electron energy increase and exceed their prestorm levels due to either injection of energetic electrons from the interplanetary medium into the trapping zone or some acceleration process connected with the geomagnetic disturbance. This phenomenological pattern was confirmed later by numerous observations of relativistic electron fluxes in the heart of the ORB [Arnoldy et al, 1960;Hoffman et al, 1962;Forbush et al, 1962]. Direct comparison of the electron fluxes in the ORB and in the interplanetary medium [Van Allen and Lin, 1960] shown that the ORB was developed over 2-day period after the storm maximum and it contained several thousand times the intensity of electrons that was present in the original solar plasma cloud before its arrival at the Earth.…”
Section: Introductionmentioning
confidence: 71%